Hormon Progesteron Feses Pada Kambing Peranakan Ettawah Bunting: Progesterone Hormon of Feces on the Pregnant Ettawah Goat - Claude Mona Airin; Amelia Hana; Sarmin; Pudji Astuti (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2022)
Abstract  The main obstacle of invasive hormone research of Etawah crossbreed goats (PE) were the sample collection due to the aggressiveness of PE goats. Improper ways of handling the goats would result in stress which leads to bias on the data. This research aims to determine the level of fecal progesterone of PE goats during pregnancy. This research use 5 pregnant and 5 non-pregnant PE goats. Diagnosis of pregnancy was conducted by observing the absence of estrus after breeding. Fecal collection was conducted in week 4, 8, 12, 16, 20, and 2 weeks after parturition but sample collection of non-pregnant goats conducted once. The sample of fecal which has been collected then frozen and extracted using methanol 80% as much as 3 ml. The fecal extract was analyzed using EIA KIT progesterone. The results of measurement of fecal progesterone level were 6,282 ± 950.96 ng/gr of feces (week 4 of pregnancy); 18,391.8 ± 2,584 ng/gr (week 8 of pregnancy); 25,958.4 ± 3,447.1 ng/gr of feces (week 12 of pregnancy); 25,233.4 is ± 3,306 ng/gr of feces (week 16 of pregnancy); 18,238.2 ± 3,069.5 ng/gr of feces (week 20 of pregnancy). The level of fecal progesterone in 2 weeks after giving birth was 516 ± 228.16 ng/gr of feces. Meanwhile, the level of fecal progesterone of non-pregnant PE goats is 254.2± 214.5 ng/gr of feces. The conclusion of the progesterone level of PE goats during pregnancy can be detected using the sample of feces with the highest level in week 12 of pregnancy.  Keywords: Feces; Non-invasive; PE Goats; Progesterone   Abstrak  Kendala utama penelitian hormonal secara invasive pada kambing Peranakan Ettawah (PE) pengambilan sampel pada hewan tersebut karena karakteristik kambing PE yang sangat agresif. Handling yang tidak tepat dapat menjadi stresor yang akan menghasilkan data yang bias. Penelitian ini bertujuan untuk mengukur kadar hormon progesteron feses pada kambing PE selama kebuntingan. Penelitian ini menggunakan 5 ekor kambing PE bunting dan 5 kambing PE tidak bunting. Diagnosa kebuntingan dilakukan dengan pengamatan tidak munculnya estrus setelah pengawinan. Pengambilan feses dilakukan pada minggu ke 4, 8, 12, 16 dan ke 20 dan 2 minggu setelah partus. Pada kambing tidak bunting, pengambilan sampel dilakukan 1 kali. Sampel feses yang telah terkumpul, dikeringbeku dan kemudian diekstraksi menggunakan methanol 80% sebanyak 3 ml untuk selanjutnya dianalisis menggunakan KIT Progesteron (Calbiotech R - USA). Hasil uji pararelism menunjukkan adanya penurunan OD secara paralel seiring dengan besarnya pengenceran sampel. Kadar progesteron feses didapatkan, 6.282  ± 950.96 ng/gr feses (minggu ke 4 kebuntingan); 18.391,8 ± 2584 ng/gr fese (minggu ke 8 kebuntingan); 25.958, 4 ± 3.447,1 ng/gr feses (minggu ke 12 kebuntingan); 25.233,4 ± 3.306 ng/gr feses (minggu ke 16 kebuntingan); 18.238,2 ± 3.069,5 ng/gr feses (minggu ke 20 kebuntingan). Kadar progesteron feses 2 minggu setelah melahirkan adalah 516 ± 228,16 ng/gr feses sedangkan progesteron kambing PE tidak bunting adalah 254,2 ± 214,5 ng/gr feses. Kesimpulan kadar progesteron kambing PE selama kebuntingan dapat dideteksi menggunakan sampel feses dengan kadar tertinggi pada minggu ke 12 kebuntingan. Kata Kunci: Feses; Kambing PE, Non-invasif, Progesteron